Analisis Proksimat pada Batubara (Ash Content) di Laboratorium PT Superintending Company of Indonesia (SUCOFINDO) Cabang Padang - Salsabila Salsabila; Sri Benti Etika (MASALIQ, 2025)
Indonesia possesses economically valuable coal deposits distributed across the Tertiary basins of the western Sunda Shelf, particularly on the islands of Sumatra and Kalimantan, positioning the country as one of the world’s leading coal producers. This study aims to determine the ash content of coal samples from various mining sites. Samples were analyzed using the proximate analysis method to measure parameters including total moisture (TM), inherent moisture (IM), ash content (ASG), and fixed carbon (FC). This method enables the identification of variations in coal characteristics resulting from differences in mining origins. The results indicate that TM, IM, ASG, and FC levels vary across samples, reflecting differences in geological conditions and coal quality. The total moisture and fixed carbon values obtained from crucible 1 and crucible 2 were both recorded at 6%. The study concludes that coal characteristics differ by source, and proximate analysis provides a valuable preliminary insight into quality assessment. These findings serve as a foundation for developing more accurate and efficient coal analysis methods and offer a reference for industrial applications and energy research.